Overtraining syndrome in athletes. A comprehensive review and novel perspectives - Cadegiani, F. (Springer Nature, 2020)
This book discusses major changes in our understanding of the most prevalent non-orthopedic, sports-related condition - overtraining syndrome (OTS), arguing that it should be considered as the manifestation of burnout in athletes, rather than simply the result of excessive training.